Reactions of N-Hydroxy-N-o-Tolyl-N´ -(2-Methyl) Phenyl Benzamidine Hydrochloride with Various Metal Ions - Mishra, Alok; H. Mohabey, Miss (Asian Journal of Chemistry, 2010)
Reactions of N-hydroxy-N-o-tolyl-N´-(2-Methyl) phenyl benzamidine hydrochloride (HTPMBH) with different metal ions have been studied in the present investigation. Studies reveal that the reagent reacts with Cu(II) and Ni(II) to form water-insoluble complexes of definite composition. These complexes are thermally stable. Gravimetric estimation of these metal ions can be carried out using this reagent. V(V) forms violet water-insouble complex which can be extracted in chloroform in 1 M to 10 M acetic acid. The extraction is quantitative and can be utilised for spectrophotometric determination of V(V). Fe(III) forms orange-red complex extractable in benzene in presence of thiocyanate. The mixed ligand complexes of iron(III), vanadium(V) and molybdenum(V) show the promising results of using the reagent for selective extraction and subsequent determination of these metals.